Shariah Compliance and Governance Accountability in Disaster Aid Distribution: A Comparative Analysis of Aceh Tamiang and Padang Flash Flood Relief Operations - Irham Dongoran; Ahmad Nizar (Program Studi Hukum Ekonomi Syariah STAI As-Sunnah Deli Serdang, Sumatera Utara, 2026)
This article examines the shariah compliance and governance accountability mechanisms employed in two Islamic higher education institution-led disaster relief operations in Indonesia during late 2025. Drawing on empirical data from documented relief distributions in Aceh Tamiang (November 2025) and Padang, West Sumatra (December 2025), the study analyzes how Islamic legal principles of amanah (trustworthiness), transparency, and adl (justice) were operationalized in emergency humanitarian contexts. The research employs comparative case analysis to evaluate governance structures, accountability mechanisms, fund management protocols, and beneficiary verification systems across both operations. Findings reveal that while both institutions implemented systematic beneficiary registration and transparent fund sourcing, critical governance gaps emerged in third-party oversight, standardized verification protocols, and formal shariah audit mechanisms. The Aceh operation distributed Indonesian Rupiah 138,500,000 to 270 households through multi-stakeholder coordination, while the Padang operation channeled Rupiah 57,000,000 to 150 households via international Islamic philanthropy networks. Both cases demonstrate adaptive governance responding to emergency conditions, yet lack formalized shariah compliance frameworks required for institutional Islamic finance operations. The article contributes to Islamic Economic Law scholarship by identifying specific regulatory deficits in disaster-related sadaqah governance and proposing a five-tier shariah accountability framework for emergency humanitarian operations undertaken by Islamic institutions.